ENERGY EFFICIENCY AND HEAT INTEGRATION IN THE SYRUP PRODUCTION PROCESS - Guevara Orozco, Lisandra; Guirola Céspedes, Claudia; Hernández Touset, Juan Pedro (Centro Azúcar Journal, 2025)
Introduction: The rational use of energy is of great importance in current times due to the scarcity of fossil fuels, their increase in cost and the negative impact they have on the environment. As a consequence of this, the terms of process integration are being handled, which allow reducing materials and energy consumption, as well as reducing gas emissions into the atmosphere. Objective: To evaluate the energy performance of syrup production and apply Process Integration (PI) to achieve potential savings in material and energy resources. Materials and methods: To determine and analyze the energy performance indicators (IDEns), the thermoenergy balance methodologies are applied, while the Pinch Analysis methodology is applied to the analysis and design of the heat exchanger network. Results and discussion: The results show the possibilities of energy savings being able to recover 95% of the maximum recoverable energy (MER). Conclusions: Syrup production presents several challenges in terms of its energy performance with inadequate management of heat recovery and steam generation. The results obtained through the construction of the problem table indicate that the process does not require cooling service. With the IP, annual savings of 526 525.79 can be obtained in fuel and cooling water.